Development of Financial Infrastructure in India: Past and Contemporary Initiatives. - Bhole, L.M (2006)
Financial sector reforms in India have been widely discussed, supported, and commended. While doing so, the financial policy before the introduction of the reforms has not been properly and adequately assessed; while its strengths or positive features have been taken for granted, its failures have been grossly overplayed. The objective of this paper is to try to correct this imbalance. It compares the policies, approaches, and issues involved in the development of the financial infrastructure in India during 1951-91 and after 199I. The paper illustrates that the approach and initiatives towards financial development in India before 1991 were more sound as compared with those after 1991. Financial sector reforms have tended to weaken the Indian financial system by increasing its instability, volatility, inequity, crises, and so on. The restrengthening of the infrastructural role of the Indian financial system, inter alia, requires suitable regulatory arrangements, financial decentralization, and realization of the importance of the role of ethics in the area of finance.